2020
DOI: 10.1021/acsami.0c00013
|View full text |Cite
|
Sign up to set email alerts
|

Structural Engineering of Two-Dimensional Covalent Organic Frameworks for Visible-Light-Driven Organic Transformations

Abstract: Covalent organic frameworks (COFs) emerging as a novel kind of visible light-responsive organic semiconductor have attracted extensive research attention in the field of photocatalytic organic transformations. However, the key parameters affecting their photocatalytic properties are still not clear. In this work, a series of [3 + 3] COFs with similar two-dimensional hexagonal structure but different compositions are synthesized and employed as model materials for investigating the key factors affecting the pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
78
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 100 publications
(79 citation statements)
references
References 58 publications
1
78
0
Order By: Relevance
“…Recently, Yang and co-workers also established a series of COFs (OH-TFP-TTA, OH-TFP-TAPB et al Figure 4, Table 2) to catalyze the dehalogenation reaction and aerobic CDC reaction (Scheme 13, c, d). [53] In this work, the author found that the incorporation of hydroxyl group enhanced the photocatalytic activity by narrowing the band gap of COFs and thereby promoting charge separation efficiency and conductivity. Moreover, Zhang et al reported an asymmetric CTF (asy-CTF, Figure 4, Table 2) to catalyze the synthesis of benzophosphole oxides (Scheme 15, a).…”
Section: Photoelectric Properties Of Cofs In Catalytic Organic Synthesismentioning
confidence: 96%
“…Recently, Yang and co-workers also established a series of COFs (OH-TFP-TTA, OH-TFP-TAPB et al Figure 4, Table 2) to catalyze the dehalogenation reaction and aerobic CDC reaction (Scheme 13, c, d). [53] In this work, the author found that the incorporation of hydroxyl group enhanced the photocatalytic activity by narrowing the band gap of COFs and thereby promoting charge separation efficiency and conductivity. Moreover, Zhang et al reported an asymmetric CTF (asy-CTF, Figure 4, Table 2) to catalyze the synthesis of benzophosphole oxides (Scheme 15, a).…”
Section: Photoelectric Properties Of Cofs In Catalytic Organic Synthesismentioning
confidence: 96%
“…Similar as COF-JLU22, the photocatalytic activity of another three kinds of DÀ A COFs containing electron-donating triphenylbenzene, that is, 1,3,5-tri(4-formylphenyl)benzene (TFP), 1,3,5-tris(4-formyl-3-hydroxyphenyl)-benzene (OH-TFP), 1,3,5-tris (4-formyl-3-trifluoromethyl)benzene (CF 3 -TFP), and electron-accepting triphenyltriazine (TTA) segments toward dehalogenation of phenacyl bromide was also evaluated. [59] The reaction was carried out by green light irradiation for 18 h. Results indicated that the COF incorporating OH-functionalized triphenylbenzene moieties showed higher catalytic activity (reaction conversion:~90 %) than the ones containing CF 3 -and Hsubstituted triphenylbenzenes, which was attributed to the narrower bandgap, more efficient charge separation and high conductivity of the OH-containing COF. Besides, OH-TFP-TTA COF as catalyst demonstrated high recyclability.…”
Section: Catalysts For Organic Transformationmentioning
confidence: 99%
“…In general, the formation of D−A arrays by polycondensation between donor and acceptor monomers are essential for a typical D−A COF. Thus far, only a few boronic‐ester‐, [14,34,35,46,47,49,51,63] imine‐ [40b,41b,42,48a,52–62] and C=C‐linked [44] D−A COFs have been reported (Scheme 1).…”
Section: D‐a Cofmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from photoelectric properties, the porosity could also have significant influence on the catalytic activity. [7,35] The lower activity of nTp-TTA/POM-1.1 is possibly related with its low surface area. The nTp-TTA/ POM-4.1 with narrow bandgap exhibited lowest activity among nTp-TTA/POM-x samples, possibly due to its low charge separation rate.…”
Section: Pw 12 O 40mentioning
confidence: 99%